The Course of Subjective Sleep Quality in Middle and Old Adulthood and Its Relation to Physical Health - Sakari Lemola; David Richter (The Journals of Gerontology Series B: Psychological Sciences and Social Sciences, 2013)
Objectives. Older adults more often complain about sleep disturbances compared with younger adults. However, it is not clear whether there is still a decline of sleep quality after age 60 and whether changes in sleep quality in old age are mere reflections of impaired physical health or whether they represent a normative age-dependent development.Method. Subjective sleep quality and perceived physical health were assessed in a large sample of 14,179 participants (52.7% women; age range 18–85) from the German Socio-Economic Panel Study across four yearly measurement time points.Results. Subjective sleep quality linearly declined from young adulthood until age 60. After age 60, a transient increase in subjective sleep quality occurred that coincides with retirement. After age 66, subjective sleep quality appears to decrease again. Physical health prospectively predicted subjective sleep quality and vice versa. These relations were similar for participants aged over and under 60.Discussion. Around retirement, a transient increase in subjective sleep quality appears to occur, which might reflect a decrease in work-related distress. Perceived physical health appears to be important for subjective sleep quality in old adults but not more important than at younger age.
Additional information: This is a pre-copy-editing, author-produced PDF of an article accepted for publication in The Journals of Gerontology Series B: Psychological Sciences and Social Sciences following peer review. The definitive publisher-authenticated version "The Course of Subjective Sleep Quality in Middle and Old Adulthood and Its Relation to Physical Health / Sakari Lemola, David Richter. In: Journals of Gerontology. Series B, Psychological Sciences and Social Sciences 68 (2013), 5, S. 721-729" is available online at: http://dx.doi.org/10.1093/geronb/gbs113.
Keywords: 330; German Socio-Economic Panel Study; Old age; Physical health; Retirement; Sleep quality; Alter; Rentner; Gesundheit; Panel; Schlaf